Effect of Preparate Coloring Delay Achid Resistant Bacteria With Ziehl Neelsen Method On The Result of Microscopic Examination - Misnarliah; Mudrika; Anastasia A Basir (International Journal of Science, Technology & Management, 2021)
The microscopic examination of smear from sputum specimens plays an important role in the initial diagnosis and monitoring of pulmonary TB treatment. The Ziehl Nelseen method is the method for examining acid-resistant bacteria smear recommended by WHO. This method has high specificity for detecting acid-resistant bacteria in sputum. This study aims to determine the effect of postponement of sputum smear staining on the quality of acid-resistant bacteria germs on the results of microscopic examination using the Ziehl Nelseen staining method. The length of time to delay staining used was 3 days, 2 days and the control was direct preparations staining. The sample used was positive smear sputum. The results showed that from 10 samples of sputum, the results obtained were directly stained with results of 1+ there were 7 samples, and 2+ there were 3 samples, while the samples with the preparations were delayed for 2 days and 3 days at room temperature, respectively +1 as many as 7 samples, and 2+ as many as 3 samples. However, there was no difference in the reading of the staining results between the direct stained samples with the stained preparations with a delay of 2 days and 3 days at room temperature. The results of this study still have many shortcomings and to improve them it is recommended to carry out further research with a larger scale and sample size.